Comparing Journalistic Cultures - Hanusch, Folker (Taylor & Francis Ltd (Sales), 2020)
This book offers an analysis of journalists’ professional views against a variety of political, economic, social, cultural, and linguistic contexts. Based on data gathered for the Worlds of Journalism Study, which conducted surveys with more than 27,000 journalists in 67 countries, the authors explore aspects such as linguistic and religious influences on journalists’ identities, journalists’ views of development journalism, epistemic issues, as well as the relationship between journalism and democracy. Further, the book provides a history of the evolution of the Worlds of Journalism Study, as well as the challenges of conducting such comparative work across a wide range of contexts. A critical review by renowned comparative studies scholar Jay Blumler offers food for thought for future endeavours. This unprecedented collaborative effort will be essential reading for scholars and students of journalism who are interested in comparative approaches to journalism studies and who want to explore the wide variety of journalism cultures that exist around the globe. It was originally published as a special issue of Journalism Studies.
https://katalog.adlr.link/Record/51-9781032087122